Growing Man-Leopard Conflicts in Gujarat State, India - Singh, H. S. (Indian Forester, 2006)
Population of leopard is on increase in Gujarat State and has doubled during last two decades as a result of conservation measures. Population management is a new challenge to wildlife managers to reduce increasing man-leopard conflicts in some areas, especially around Gir and in Panchmahals where concentration of the animal is beyond tolerance limit. Unlike other cats, leopard is capable of exploiting degraded habitats, rocky hills and ravines for shelter and uses village sites in night to manage food by killing domestic animals, mainly goats, sheep and dogs. Level of man-leopard conflict has season variation in the study area due to change in availability of food and water. Average data of last eleven years reveals that summer (May/June) predation on resident livestock was 2.5 times higher than the predation in winter (February). Removal of some leopard from high concentrated area, especially problem animals, improvement of herbivore population, translocation of wild boar and hanuman langur from problem areas to the leopard populated zone and implementation of water hole management plan in summer may be some options to reduce the conflicts in the state.